2000
DOI: 10.1590/s0036-46652000000200003
|View full text |Cite
|
Sign up to set email alerts
|

ELISA test for the diagnosis of cysticercosis in pigs using antigens of Taenia solium and Taenia crassiceps cysticerci

Abstract: SUMMARYIn the present study ELISA was standardized for the diagnosis of swine cysticercosis based on necropsy parameters and confirmed positive and negative control sera. Serum samples from pigs with other infections were also assayed to determine possible crossreactions. Four antigens were assayed: from Taenia crassiceps vesicular fluid (VF-Tcra) and crude larvae extract (T-Tcra), and from Taenia solium extracts of scolex (S-Ts) and of larvae (T-Ts). A checkerboard evaluation of antigen, serum and conjugate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
0
12
0
5
Order By: Relevance
“…The ELISA test was performed as described by Pinto et al (2000), with some modiϐications. The optimal dilutions of antigens, test serum samples and conjugate were determined through checkerboard titration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ELISA test was performed as described by Pinto et al (2000), with some modiϐications. The optimal dilutions of antigens, test serum samples and conjugate were determined through checkerboard titration.…”
Section: Methodsmentioning
confidence: 99%
“…These results corroborate those described by Boa et al (2002), who found that only 10.6% of metacestodes are present in muscles or organs indicated for the search of cysticercosis. As detailed necropsy of pig carcasses followed by the enumeration of cysticerci (considered here as the golden standard) is time-consuming and expensive, it is therefore impractical for traditional inspection and would lead to commercial losses (Gonzalez et al 1990, Pinto et al 2000.…”
Section: Detection Of Circulating Antigen Using Ag-elisamentioning
confidence: 99%
See 1 more Smart Citation
“…Ao utilizar os mesmos critérios para seleção do ponto de corte 1 e 2, contudo adicionando 3 SD, pôde-se observar que do total de amostras somente 4 apresentaram-se como positivas para o ponto de corte 1 (sensibilidade de 1,99%), e para o ponto de corte 2, foi possível confirmar 29 amostras positivas (sensibilidade 14,4%). De acordo com Pinto et al (2000) quando o ponto de corte é aumentado para 3SD é previsível a queda da sensibilidade do teste.…”
Section: Resultsunclassified
“…Vale ressaltar que a utilização de 2 ou 3 SD como critério de ponto de corte é dependente do objetivo dos ensaios, visto que, a utilização de 3 SD é mais apropriado para fins de diagnóstico e 2 SD para testes de triagem ou seleção (PINTO et al, 2000). Paulan et al (2013) relatam também a correlação entre ponto de corte e taxa de sensibilidade do ELISA.…”
Section: Discussionunclassified